2020
DOI: 10.1002/jcla.23416
|View full text |Cite
|
Sign up to set email alerts
|

Severe renal impairment as an adverse prognostic factor for survival in newly diagnosed multiple myeloma patients

Abstract: Background Renal impairment (RI) is associated with poor survival in newly diagnosed multiple myeloma (MM) patients. Renal function recovery has been one of the main therapeutic goals in those patients. Methods The records from 393 newly diagnosed MM patients in our hospital between January 2012 and December 2016 were retrospectively analyzed. RI was defined as an eGFR < 40 mL/min according to the novel IMWG criteria. RI patients were categorized based on their renal function at diagnosis: severe RI: eGFR < 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
(105 reference statements)
0
15
0
Order By: Relevance
“…RI and worsening renal function is a known high-risk factor for both NDMM and RRMM that is associated with poor OS [55,56]. Between 20% and 50% of patients have RI at diagnosis, which may be caused by cast nephropathy, light chain deposition disease, AL amyloidosis, and hypercalcaemia [55,57].…”
Section: Ri Is Common In MM and Is Associated With Poor Survivalmentioning
confidence: 99%
“…RI and worsening renal function is a known high-risk factor for both NDMM and RRMM that is associated with poor OS [55,56]. Between 20% and 50% of patients have RI at diagnosis, which may be caused by cast nephropathy, light chain deposition disease, AL amyloidosis, and hypercalcaemia [55,57].…”
Section: Ri Is Common In MM and Is Associated With Poor Survivalmentioning
confidence: 99%
“…The median OS of patients with an eGFR ≥ 40 mL/min is about 51 months compared to only 17 months in patients with an eGFR < 40 mL/min. Achieving renal response is associated with improved survival [ 80 , 81 ]. Renal response occurs when renal impairment is reversed by treatment.…”
Section: Patient-related Factors With Impact On Decision-makingmentioning
confidence: 99%
“…Studies have shown that RI is associated with reduced overall survival (OS) and increased risk of early mortality in MM, 5 , 10 , 11 with some suggesting a correlation between outcomes and degree of estimated glomerular filtration rate (eGFR) decline. 4 , 10 A recent meta-analysis 12 of six randomized controlled trials conducted through 2019 found that RI conferred a higher relative risk of disease progression or death among participants. Improvements in both OS and renal function have been reported with novel treatments for RRMM, particularly when compared to conventional chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in both OS and renal function have been reported with novel treatments for RRMM, particularly when compared to conventional chemotherapy. 10 Though improvement in renal function is associated with improved survival, OS remains inferior among patients with baseline RI compared to those with no RI at MM diagnosis. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation